Behind the 2008 Capital Market Collapse - C-René Dominique (Economics and Econometrics Research Institute (EERI), 2008)
Greed and the unethical behavior of financial institutions obviously played a part in the collapse of the world capital market in 2008. But, this paper argues that the main culprits are the neo-liberal ideology (requiring ever smaller gov-ernments and privatization) and the flawed theories of risk assessment. It also finds that given the fact that market economies are fractal structures, the objective assessment and / or the quantification of risks is not even possible. It concludes with some recommendations as to how to avoid future collapses.
Keywords: E22; 330; Efficiency and self-correction in market economies; Linear-positive and non-linear modelings; creative destruction of coefficients; determinism and randomness; and risk assessment